N,Cu-CD-Decorated Mesoporous WO3 for Enhanced Photocatalysis Under UV–Vis–NIR Light Irradiation - Ni, Tianjun; Li, Qiansheng; Yan, Yunhui; Yang, Zhijun; Chang, Kaiwen; Liu, Guoguang (Frontiers in Materials, 2021)
Research on the design of semiconductor photocatalysts with rapid electron transfer efficiencies and broad-spectrum responses for environmental remediation remains a pressing challenge. Herein, we described the fabrication of a novel broad-spectrum nitrogen and copper co-doped carbon dots/mesoporous WO3 nanocomposite (N,Cu-CDs/m-WO3), with complete UV–vis–NIR spectrum response, light harvesting capabilities, rich oxygen vacancies, rapid electron transfer abilities, low electron-hole (e-/h+) pair recombination rate and extensive specific surface area. Under 2h of UV-vis-NIR light exposure the N,Cu-CDs/m-WO3-0.8 nanocomposite showed excellent photodegradation efficiencies for rhodamine B (RhB) of 81.5%, 97.6%, and 56.2%, respectively. The nanocomposite exhibited extremely high photocatalytic activities for methylene blue (MB), tetracycline hydrochloride (TCH), oxytetracycline (OTC), ciprofloxacin (CIP), and bisphenol A (BPA). Moreover, we found that the conversion between Cu (II) and Cu (I) played a key role in accelerating electron transfer and inhibiting the recombination of e-/h+ pairs. This work provides an efficient strategy for the full-spectrum utilization of solar light and enhanced electron transfer capacities in the semiconductor photocatalysis field.